Outline of the Evolution of the Hungarian Monetary Policy from the Restoration of the Two-level Banking System to the Present Day - Lentner, Csaba (Public Governance, Administration and Finances Law Review, 2021)
This study outlines the development of Hungary’s monetary policy, and the course and changes in its objectives and instruments since the beginning of the market economy transition in the late 1980s. The author’s basic thesis is that the period since the two-level banking system was reinstated after four decades of a planned economy system, in 1987, can be basically divided into three development phases with significantly different characteristics. The first phase was an ‘attempt to introduce’ an imported monetary mechanism, or perhaps an urge to comply with it, while the second phase was an approach of a monetary regime change launched in 2013 and supporting economic growth and financial stability strongly and directly, which lasted until the appearance of the traumatic elements of the Covid-19 pandemic crisis. The third phase is evolving today, under the circumstances of adapting to the conditions of the real essence of the twenty-first century, i.e. a new type of international competitiveness, which is pursued by the Central Bank of Hungary as stipulated by the Fundamental Law and the cardinal Central Bank Act of Hungary.